Trade Secret Leaks Via Digital Media Comparative Analysis Of Indonesia And Thailand: Pembocoran Rahasia Dagang Melalui Media Digital Analisis Komparatif Indonesia Dan Thailand - Ismawati Ismawati; Ramadhina Eka Putri Sugiarto; Arzetty Putri Septeddy; Suria Suria; Binsar Pandapotan Panjaitan; Lia Nuraini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid evolution of electronic technology presents significant challenges for business information security, escalating the risk of corporate data breaches. Specific Background In Indonesia, recent incidents involving corporate data misappropriation by current or former personnel via electronic platforms demonstrate the severe economic and reputational vulnerabilities facing modern enterprises. Knowledge Gap Although Indonesia implements Law Number 30 of 2000, this statute fails to explicitly address electronic breaches, necessitating fragmented reliance on multiple ancillary regulations, whereas comparative jurisdictions possess more adaptive legal frameworks. Aims This study analyzes the regulatory efficacy of electronic commercial information protection and compares the statutory frameworks between Indonesia and Thailand. Results Utilizing a normative legal and comparative approach, findings reveal that Indonesian statutes lack explicit provisions for electronic leaks, digital evidence, and post-employment confidentiality, resulting in legal uncertainty and inefficient enforcement. Conversely, Thailand’s Trade Secrets Act (No. 2) B.E. 2558 demonstrates superior adaptability by explicitly accommodating electronic commercial information, recognizing digital evidence, and establishing specialized dispute resolution mechanisms. Novelty This research distinctly isolates the electronic dimensions of commercial misappropriation by former personnel, bridging theoretical legal certainty paradigms with practical comparative legislative solutions from a neighboring nation. Implications Consequently, Indonesian lawmakers must urgently modernize the corresponding laws to integrate electronic evidence standards, define virtual asset boundaries, and explicitly regulate former personnel liabilities to ensure robust legal certainty. Highlights Current national laws fail to explicitly address electronic corporate data breaches. Thai legislation explicitly accommodates electronic evidence and post-employment confidentiality liabilities. Modernizing national statutes ensures robust legal certainty for commercial information owners. Keywords Electronic Evidence; Legal Certainty; Corporate Data Security; Post-Employment Confidentiality; Legislative Modernization